Effect of Promotion and Service Quality on Customer Satisfaction at PT. Surya Karya Prima in Jakarta - Triyadi Triyadi (Pendidikan Administrasi Perkantoran, Universitas Negeri Makassar, 2020)
Fulfillment of customer desires becomes very important in determining the quality of service, because what determines whether or not the quality of service is not producers or companies but consumers. This study aims to determine the effect of promotion and service quality on customer satisfaction at PT. Surya Karya Prima in Jakarta. The method used was explanatory research with a sample of 100 respondents. The analysis technique uses statistical analysis with regression testing, correlation, determination and hypothesis testing. The results of this study have a significant effect on customer satisfaction by 38.7%, hypothesis testing obtained significance 0,000 <0.05. Service quality has a significant effect on customer satisfaction by 48.5%, the hypothesis test obtained significance 0,000 <0.05. Promotion and quality of service simultaneously have a significant effect on customer satisfaction by 56.0%, hypothesis testing obtained significance 0,000 <0.05.